PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN PROMOTOR PADA PT.SHARP ELEKTRONIK CABANG PEKANBARU - Dzikra, Faira Medina (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the effect of incentives on the performance of promoter employees at PT. Sharp Electronics Pekanbaru Branch. Method: The research employs a quantitative approach with descriptive methods and simple linear regression analysis. The sample consists of 44 promoter employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using validity, reliability, normality tests, and hypothesis testing (t-test and coefficient of determination). Results: The results indicate that incentives have a significant effect on employee performance, with the regression equation Y = 3.768 + 0.633X. The coefficient of determination (R²) of 0.727 shows that 72.7% of the variation in employee performance is influenced by incentives, while the remaining percentage is attributed to other factors. Keywords: Incentives, Employee Performance.